As relações de interação e integração entre cérebro, corpo-propriamente-dito e meio-ambiente na constituição da mente consciente - Cardoso, Thiago Rezende de Deus (2016)
This dissertation will be marked by our proposal to hold a theoretical perspective to the classical mind-body problem, and more precisely for the defense of the idea that consciousness (or conscious mind) emerges from the interaction and integration relationships between body proper, brain and environment. This purpose will lead us to assume an alternative position with respect to the more traditional perspectives to the mind-body problem, ie an alternative perspective not only in relation to the dualistics forms of mind-body, but also in regards to the reductive physicalists, which usually reduces mind to brain. Aiming to support a position that both avoid the idea that mind and body are distinct substances and the theory that the brain explains the consciousness in its totality, we will dedicate an important part of this work to explain how the structure of consciousness depends significantly of the body proper and the bodily information mechanisms as well as the environment and the physiological mechanisms through which we place ourselves in space, in front of us and the other bodies (organic and inorganic). Given that the relationship between brain, body and environment involves different mental levels — from the most primitive and unconscious mental mechanisms until conscious and sophisticated levels — we will proceed to the task of assuming a model to explain in what sense these levels contribute to that our instincts and the most sophisticated dimensions of our mental life are part of the one and the same process, which is why we will structure our argument from the ideia that mind, self, and consciousness are the different hierarchical levels which make up the totality of our psychic life and therefore organic one. Imbued with this conceptual approach, we will advance to the focus of this work, namely the reasons that will lead us to give a prominent role to the body proper and the environment in the constitution of the conscious mind, or even the reasons that will lead us to defend the thesis according to which we are embodied and situated, as well as the reasons that will lead us to reject the theoretical positions that dichotomize man and world. In order to support the thesis that we are embodied and situated, and therefore with the purpose of overcoming the theoretical paradigms that dichotomize consciousness and world, we will turn out to the authors and the perspectives we believe to be more successful in this endeavor, including the phenomenological approaches to bodily self-consciousness, the enactivists perspectives and the researches dedicated to mapping the interaction and integration relationships between brain, body and environment. To achieve our goals, the dissertation will be divided into two chapters: the first chapter will emphasize in what way the structuring of consciousness depends on the body proper and the environment, while in the second chapter we will resort to the phenomenological dimensions of bodily self-consciousness, emphasizing the bodily information channels that provide us the immediate certainty, in a first person perspective, that the self is bodily in a non-metaphorical sense.